Implementasi Kebijakan Pengendalian Pertumbuhan Penduduk di Kabupaten Sidoarjo - Diro, Ana; Arsiyah, Arsiyah (Universitas Muhammadiyah Sidoarjo, 2014)
The purposes of this research was analyzing and describing the policy implementation of controlling population growth in Sidoarjo Regency. This research was using a source of data consists of primary and secondary data with collecting techniques of data namely: observation, interview and documentation. Data analizing technique used qualitative analysis with descriptive approach that included: collecting of data, reduction of data, presentation of data, draw a conclusion. This result of this research indicated that information education communication was still lacking and giving services to the public and lacked of planning family trainer, the duty of planning family was rising, the participate of planning family for man still low especially medical man surgery, and population growth is quite high.